A parallel spatio–temporal model for emergency evacuation simulation. (1st January 2015) - Yang, Bo; Ren, Bo
The research provides a new way to simulate emergency evacuation in a large–scale environment based on multi–resolution modelling (MRM). The authors provide a parallel spatio–temporal model to synchronise and control two kinds of resolution models: the micro model based on multi–agent system (MAS) and particle swarm optimisation (PSO) algorithm, and the macro model based on a fluid dynamics model. With this approach, it is possible to apply distributed simulation to a large–scale emergency evacuation, while the individual behaviours at specific locations can be also presented.